Development and Validation of a Checklist for Safe Blood Transfusion in Anesthesia: A Methodological Study - Shahriyar Mahdizadeh; Parisa Moradimajd; Shaqayeq Taghizadeh; Jamileh Abolghasemi; Shahnam Sedigh Maroufi (Health Science Reports, 2026)
ABSTRACT Background and Aims Blood transfusion is a vital and life‐saving intervention in medical care and anesthesia that saves millions of lives worldwide each year. Therefore, ensuring safety at every stage of the transfusion process is essential. Accordingly, the present study aimed to develop and psychometrically validate a checklist for safe blood transfusion during anesthesia. Methods This methodological descriptive–analytical study was done between December 2024 and April 2025. Initially, a comprehensive literature search was performed using electronic databases and reputable scientific sources. Existing blood transfusion checklists used in healthcare settings were reviewed, and relevant items were extracted to create an item pool. The Australian Blood Transfusion Checklist was selected as the foundational framework. Subsequently, brainstorming sessions were held with experts in anesthesia and hematology, resulting in a preliminary checklist draft. Face and content validity were assessed using the impact factor (IF), content validity index (CVI), and content validity ratio (CVR). Checklist reliability was evaluated using inter‐rater agreement, Cronbach's alpha coefficient, and intraclass correlation coefficient (ICC). Results The initial draft included 30 items. All items met the face validity criterion, with an IF > 1.5. Regarding content validity, based on the evaluations of 11 experts and according to Lawshe's table, 28 items achieved a CVR above 0.59. Two items that did not meet the acceptable CVI or CVR thresholds were excluded from the final checklist. Cronbach's alpha for the entire instrument was 0.828, and ICC for inter‐rater reliability was 0.976 (95% CI: 0.967–0.983; p < 0.001). The final checklist comprised 28 items organized into 13 subcategories. Conclusion The findings indicate that the developed checklist for safe blood transfusion during anesthesia is a reliable tool for use in anesthesia settings. The implementation of this checklist has the potential to standardize care, reduce clinical errors, and enhance patient safety during blood administration.